2014
DOI: 10.3390/ijms150915845
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Suppression of Chaperone-Mediated Autophagy by miR-320a Promotes α-Synuclein Aggregation

Abstract: Chaperone-mediated autophagy (CMA) is involved in wild-type α-synuclein degradation in Parkinson’s disease (PD), and LAMP2A and Hsc 70 have recently been indicated to be deregulated by microRNAs. To recognize the regularory role of miR-320a in CMA and the possible role in α-synuclein degradation, in the present study, we examined the targeting and regulating role of miR-320 in Hsc 70 expression. We first constructed an α-synuclein-overexpressed human neuroblastoma cell line, SH-SY5Y-Syn(+), stably over-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 50 publications
1
46
0
2
Order By: Relevance
“…Indeed, the down-regulation of hsc70 and lamp2A in PD brains has been shown to correlate with an up-regulation of six miRNAs targeting the 3′ UTR of hsc70 or lamp2A (Alvarez-Erviti et al, 2013). However, currently there is a dearth of study material regarding the role of “CMA miRNAs” in PD pathogenesis apart from the only one study that showed the up-regulation of one of them resulted in the knock-down of hsc70 and increased levels of asyn in human SH-SY5Y neuroblastoma cells (Li et al, 2014). …”
Section: Alterations Of Cma In Pdmentioning
confidence: 99%
“…Indeed, the down-regulation of hsc70 and lamp2A in PD brains has been shown to correlate with an up-regulation of six miRNAs targeting the 3′ UTR of hsc70 or lamp2A (Alvarez-Erviti et al, 2013). However, currently there is a dearth of study material regarding the role of “CMA miRNAs” in PD pathogenesis apart from the only one study that showed the up-regulation of one of them resulted in the knock-down of hsc70 and increased levels of asyn in human SH-SY5Y neuroblastoma cells (Li et al, 2014). …”
Section: Alterations Of Cma In Pdmentioning
confidence: 99%
“…It is possible that such a punctate structure can be found in the neurons of these patients. Our data in SH-SY5Y human neuronal cells that have been studied widely as in vitro models of neuronal function and differentiation (44 -46) and in Parkinson disease (47)(48)(49), we show colocalization of 1-70 aa GFP with NFL. This is consistent with reports showing that pro-EMAP II colocalizes and binds with neurofilaments.…”
Section: Discussionmentioning
confidence: 92%
“…There are five different studies that report miRNAs that directly impact on proteolytic pathways and result in α-synuclein accumulation (Figure 3; Alvarez-Erviti et al, 2013; Decressac et al, 2013; Li et al, 2014; Zhang and Cheng, 2014; Su et al, 2016). In addition, miR-133b (Niu et al, 2016) and miR-433 (Wang et al, 2008; Schmitt et al, 2012) have been reported to impact on α-synuclein by directly targeting Ras homolog gene family, member A (RhoA) and fibroblast growth factor 20 (FGF20), respectively (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, alterations in CMA result in pathological α-synuclein accumulation. Four studies have investigated how miRNA regulation of CMA influences α-synuclein accumulation (Alvarez-Erviti et al, 2013; Li et al, 2014; Zhang and Cheng, 2014; Su et al, 2016). Firstly, Alvarez-Erviti et al (2013) transfected SH-SY5Y cells overexpressing α-synuclein with seven miRNAs that directly bind and negatively regulate two key proteins involved in CMA: Lysosome-associated membrane protein 2 (Lamp2a, hsa-miR-21*; hsa-miR-224; hsa-miR-373*; and hsa-miR-379) and Heat shock protein 70 (Hsc70, hsa-miR-26b: hsa-miR-106a*; and hsa-miR-301b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation